Pengaruh ROA dan ROE Terhadap Harga Saham - Bagus Shandy Narmaditya; Hari Wahyono; Zhenyu Li; Siti Rosnita Sakarji (Jurnal Pendidikan Ekonomi, 2024)
This study aims to systematically review the future of economic education and identify the trends and implications for policy and practice. This study adopted bibliometric analysis using VOSviewer software. The findings indicate that there has been a substantial movement over the last two decades regarding the theme of economic education. The top three countries—United States, Germany, and Indonesia contribute to this theme, whilst Universitas Negeri Malang, the University of Nebraska, and the University of Richmond are the three highest organizations that contributed to this scope during this period. The visualization from VOSviewer illustrates that the theme of economic education is linked with various dimensions. The frequency occurrence of this theme is often associated with financial literacy, pedagogy, pluralism, higher education, active learning, financial education, home economics education, teaching economics, economic literacy, heterodox economics, and entrepreneurship. The findings provide implications for concerning studies in this theme with a focus in shaping graduate students.